Classical mythology - Vandiver, Elizabeth, 1956-; Teaching Company (Chantilly, VA : Teaching Co., 2000)
In this set of 24 lectures, Professor Elizabeth Vandiver, University of Maryland, introduces the student to the primary characters and most important stories of classical Greek and Roman mythology. She also surveys some of the leading theoretical approaches to understanding myth in general and classical myth in particular.
pt. 1. lecture 1: Introduction ; lecture 2: What is myth? ; lecture 3: Why is myth? ; lecture 4: "First was Chaos" ; lecture 5: The reign of the Olympians ; lecture 7: Demeter, Persephone, and the conquest of death ; lecture 8: The Eleusinian Mysteries and the afterlife ; lecture 9: Apollo and Artemis ; lecture 10: Hermes and Dionysos ; lecture 11: Laughter-loving Aphrodite ; lecture 12: Culture, pre-history, and the "Great Goddess" -- pt. 2. lecture 13: Humans, heroes, and half-gods ; lecture 14: Theseus and the "test-and-quest" myth ; lecture 15: From myth to history and back again ; lecture 16: The greatest hero of all ; lecture 17: The Trojan War ; lecture 18: The terrible House of Atreus ; lecture 19: Blood vengeance, justice, and the Furies ; lecture 20: The tragedies of King Oedipus ; lecture 21: Monstrous females and female monsters ; lecture 22: Roman founders, Roman fables ; lecture 23: "Gods are useful" ; lecture 24: From Ovid to the stars.
DVD, region 1.
24 lectures on 4 discs, 2 discs per container.
In 2 containers (25 x 17 cm.).
Instructor: Elizabeth Vandiver, University of Maryland.
Keywords: Mythology, Classical; Mythology, Greek; Mythology, Roman